2003
DOI: 10.1176/appi.ajp.160.10.1768
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition in Schizophrenia: Intensity Effects and Error Pattern

Abstract: Patients with schizophrenia were impaired in overall emotion recognition, particularly fear and disgust, and did not benefit from increased emotional intensity. Error patterns indicate that patients misidentified neutral cues as negatively valenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
422
7
16

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 679 publications
(515 citation statements)
references
References 44 publications
(40 reference statements)
56
422
7
16
Order By: Relevance
“…Regarding the recognition of natural faces, we could replicate former findings of an emotion recognition deficit that was differential for the emotion disgust (Kohler et al, 2003;Behere et al, 2009). For the other negative emotions of fear and sadness we could show trends towards decreased performance in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Regarding the recognition of natural faces, we could replicate former findings of an emotion recognition deficit that was differential for the emotion disgust (Kohler et al, 2003;Behere et al, 2009). For the other negative emotions of fear and sadness we could show trends towards decreased performance in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 74%
“…The intensity of the stimuli could have influenced recognition rates in the present study. Kohler et al (2003) directly compared the recognition of mild versus extreme intensities of emotion in patients with schizophrenia and showed that patients were not able to profit from greater emotional intensity. In contrast, schizophrenia patients made more misattributions to other emotions when expressions were more extreme.…”
Section: Methodsological Considerations and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, although some emotional expressions have both visual and auditory components, the major channel for communicating emotions is visual via facial expressions. Thus, visual MMN might be well suited for studying the automatic perceptual component of social cognition (Astikainen & Hietanen, 2009; in disorders where it is impaired, such as in schizophrenia (Csukly et al, 2014;Kohler et al, 2003;Komlosi et al, 2013;Morris, Weickert, & Loughland, 2009). In general, VMMN might be a useful tool for studying deficits in predictive processing in cognitive domains where using visual rather than auditory stimuli is more adequate.…”
Section: Conclusion and Directions For Further Researchmentioning
confidence: 99%
“…At a higher level we have the two subdomains of understanding emotions and managing emotions. Some of the instruments studied in this field are: Bell Lysaker Emotion Recognition Task (BLERT) [59], Diagnostic Analysis of Nonverbal Accuracy 2 (DANVA2) [60], Face Emotion Discrimination Test (FEDT) [61], Penn Emotion Recognition Task (ER-40) [62]. The Bell Lysaker Emotion Recognition Task and the Penn Emotion Recognition Test were the chosen measures in SCOPE study [7].…”
Section: Arc Publishingmentioning
confidence: 99%